Melestarikan Kearifan Lokal : Keindahan Baju Bodo Bugis Makassar dalam Mempertahankan Identitas Budaya di Era Modern - Suhartini Suhartini; Nur Fauziah Kasmin; Muhammad Rasyid Ridha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the role of baju bodo as a symbol of the cultural identity of the Bugis-Makassar community and its preservation efforts in the modern era. Baju bodo is one of the oldest traditional clothes in Indonesia that has high historical, symbolic, and philosophical value. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews and literature studies. The results of the study indicate that baju bodo not only functions as a body cover, but also represents social status, local aesthetic values, and cultural wisdom that is passed down from generation to generation. The transformation of the design, color, and material of baju bodo is an adaptive strategy to remain relevant amidst the development of the times without eliminating its traditional meaning. This innovation allows baju bodo to be used in modern contexts such as formal events, education, and fashion shows. This study emphasizes the importance of collaboration between cultural communities, government, and local designers to maintain the sustainability of cultural heritage. Thus, baju bodo remains a symbol of the Bugis-Makassar cultural identity that is alive, developing, and proud in the modern era